Halalan tayyiban concept through qur'anic thematic exegesis: a study on Malaysian halal supply chain standard / Mohd Dasuqkhi Mohd Sirajuddin - Mohd Sirajuddin, Mohd Dasuqkhi (2020)
The development of any conceptual idea always needs a holistic and interconnected data to be analysed. Otherwise, the outcome will overlook some of its very pertinent elements which eventually affect the overall structure of the concept. In most of the academic discourse, the process to understand halalan tayyiban concept always begin from the Islamic rulings (hukm) perspective before transforming it into the form of standard, regulation, or law. Due to this kind of legal and ethical tendency to draft laws and regulations for halal industry, the outcomes have therefore, merely pertained to the Islamic rulings elements as the structural component of halal concept, whereas the concept itself as introduced by the Qur’an occupies ideas beyond the ruling aspects. Besides leading to the incomprehensiveness of conceptual understanding, it will also affect some of the important aspects such as the scope of halal, the context of rulings and its suitability, and overlooked some other pertinent components of halal, which are evidently exist in the Qur’an. The consistent use of “halalan tayyiban” phrase, which appears four-time in different chapters and focuses indicate that a serious conceptual idea has been presented in the Qur’an. Therefore, this thesis proposes that the most appropriate method to develop a holistics halalan tayyiban concept is through the Qur’anic thematic exegesis (QTE) where all of the phraseological aspects of related verses were analysed in order to explore the very essential elements that come from the same set of data. The four main verses are; al- Baqarah (verse 168), al-Ma’idah (verse 88), al-Anfal (verse 69), and al-Nahl (verse 114), which contain the phrase of “halalan tayiban” were analysed followed by all of the pertained verses with the word “halal” and “tayyib” existed in the Qur’an. The morphological analysis shows the very miracle of Qur’anic structure where both “halal” and “tayyib” related verses occupy the same amount of its antonym i.e. “haram” and “khabith” related verses, which all are scattered 99 times throughout the entire chapter of the Holy Book. The result reveals that a few new criteria of halalan tayyiban underlie in both conceptual and operational parts which can be considered as critical needs in halal industrial practice nowadays. They are; the halal-Kosher relation (ta‘am ahl al-kitab), naturalness or organic (tabi‘iyyah), and non-doubt (ghayr syubhah). The operational part, which is more shaped by the ruling (fiqh) aspect, on the other hand, are the non-impure (ghayr najs), safety (ghayr mudar) and the last two i.e. the non-contaminate and segregation are more shaped by the actual industrial need. As the focus of this research is limited to the Malaysian standards on halal supply chain, all the related documents contain the description about halal and halal supply chain concept were examined with all of the proposed new criteria both conceptual and operational part. A few fiqh methods also proposed to cater the need of the operational part i.e. al-talfiq (amalgamation) and al-takhayyur (selection). A mixed of quantitative and quantitative methods are employed which involve documents analysis, experts structured interviews and data analysing software i.e. the Atlas.ti